PDX1- and NGN3-mediated in vitro reprogramming of human bone marrow-derived mesenchymal stromal cells into pancreatic endocrine lineages - Limbert, Catarina; Paeth, Guenter; Ebert, Regina; Rothhammer, Veit; Kassem, Moustapha; Jakob, Franz; Seufert, Jochen (Cytotherapy, 2011)
Background aims. Reprogramming of multipotent adult bone marrow (BM)-derived mesenchymal stromal/stem cells (MSC) (BM-MSC) represents one of several strategies for cell-based therapy of diabetes. However, reprogramming primary BM-MSC into pancreatic endocrine lineages has not yet been consistently demonstrated. Methods. To unravel the role and interaction of key factors governing this process, we used well-characterized telomerase-immortalized human MSC (hMSC-TERT). Pancreatic endocrine differentiation in hMSC-TERT was induced by two major in vitro strategies: (i) endocrine-promoting culture conditions and (ii) ectopic expression of two master regulatory genes of the endocrine lineage, human neurogenin 3 (NGN3) and human pancreatic duodenal homeobox 1 (PDX1). Results. Both approaches triggered pancreatic endocrine gene expression, notably insulin, glucose-transporter 2 and somatostatin. Transgenic overexpression of NGN3 and/or PDX1 proteins not only induced direct target genes, such as NEUROD1 and insulin, and but also triggered parts of the gene expression cascade that is involved in pancreatic endocrine differentiation. Notably, ectopic NGN3 alone was sufficient to initiate the expression of specific beta-cell lineage-associated genes, most importantly PDX1 and insulin. This was demonstrated both transcriptionally by mRNA expression and reporter gene analyzes and at a protein level by Western blotting. Such reprogramming of hMSC-TERT cells induced glucose-insensitive insulin biosynthesis and secretion. Conclusions. Our results indicate that establishment of glucose-dependent insulin secretion in partially reprogrammed human MSC may depend on additional maturation factors. Moreover, hMSC-TERT provides a suitable cell model for investigating further the molecular mechanisms of reprogramming and maturation of adult MSC towards pancreatic endocrine lineages. © 2011 Informa Healthcare.
CRIS-Team Scopus Importer:2020-09-22
Keywords: Cell model; Mesenchymal stromal cells; Pancreatic endocrine lineages; Reprogramming; Telomerase-immortalized human bone marrow-derived mesenchymal stromal cell line (hMSC-TERT)